Chromosomal mapping of repetitive DNAs in the beetle Dichotomius geminatus provides the first evidence for an association of 5S rRNA and histone H3 genes in insects, and repetitive DNA similarity between the B chromosome and A complement - Cabral-de-Mello, Diogo Cavalcanti [UNESP]; Moura, R. C.; Martins, C. [UNESP] (Nature Publishing Group, 2010)
Chromosomal banding techniques and repetitive DNA mapping are useful tools in comparative analysis and in the elucidation of genome organization of several groups of eukaryotes. In this study, we contributed to the knowledge of Coleoptera genomes by reporting the chromosomal organization of repetitive DNA sequences, as well as the presence and characteristics of a B chromosome in two natural populations of Dichotomius geminatus (Coleoptera; Scarabaeidae) using classical, chromosomal banding and molecular cytogenetic techniques. As in other coleopteran species, the heterochromatin was mainly concentrated in pericentromeric regions and the B chromosome was composed almost entirely of heterochromatin. Physical mapping using double fluorescent in situ hybridization was performed for the first time in Coleoptera; using DNA probes for 5S and 18S ribosomal RNA (rRNA) and histone H3 genes, we showed that ribosomal 18S rDNAs are located in chromosomes 3 and 4, whereas 5S rRNA and histone H3 genes are colocalized in chromosomal pair 2 and show an apparently interspersed organization. Moreover, these genes are not present in the B chromosome, suggesting that the B chromosome did not originate from chromosomal pairs 2, 3 or 4. on the other hand, mapping of the C(0)t-1 DNA fraction showed that the B chromosome is enriched in repetitive DNA elements, also present in the standard complement, indicating an intraspecific origin of this element in D. geminatus. These results will contribute to our understanding of genome organization and evolution of repetitive elements in Coleoptera and other insects regarding both A and B chromosomes. Heredity (2010) 104, 393-400; doi: 10.1038/hdy.2009.126; published online 16 September 2009
Keywords: cytogenetics; C(0)t-1 DNA; FISH; genome evolution; heterochromatin; supernumerary chromosome